Distribution of Bi in the crystal structure of Bi-rich jamesonite, FePb4 (Sb5.48Bi0.52)Σ6S14 - Pazout,R. (Journal of Geosciences, 2020)
Crystal structure of Bi-rich jamesonite, FePb4Sb6S14, from Kutna Hora ore district, Czech Republic was solved from single-crystal X ray diffraction data to establish whether bismuth shows a preference for any of the three antimony sites in the structure and whether increasing content of the element is placed in one specific site in the structure or is distributed over more sites. Jamesonite is monoclinic, P21/c, with a = 4.0237(3), b = 19.1136(17), c = 15.7813(15) Å, β = 91.799(7)°, V = 1213.10(18) Å3, Z = 2, Dcalc. = 5.7746 g·cm-3. The structural formula derived from the refinement is FePb4 (Sb5.48Bi0.52)Σ6S14. The structure refinement (R = 5.22 %) of a needle-like crystal documents that out of three antimony sites in the structure, bismuth shows a preference for Sb1 and Sb3 sites in the lone-electron pair micelle of the [Pb4Sb6S13] substructure motif while the site Sb2 closest to the Fe octahedron is least inclined to accept bismuth. The refinement also reveals that bismuth content is simultaneously distributed over all three antimony sites and that the placement of bismuth first and preferentially into one antimony site does not take place.
Keywords: Bi-rich jamesonite; crystal structure; distribution of Bi; prediction; Kutna Hora; Czech Republic